A novel CSoDoA based passive islanding detection technique for multi‐DER AC microgrid control. Issue 1 (7th March 2023) - Bodda, Sivaramarao; Agnihotri, Prashant; Biswas, Santosh
Abstract: Micro‐grid islanding methods are gaining importance as the presence of renewable energy resources is becoming increasingly popular in power distribution. Among all the islanding methods, passive methods are easy to implement and applicable to all types of DERs provided the NDZ is minimized. This article presents a novel passive islanding detection method based on the CSoDoA of ellipse formed by the successive phase voltages to address the NDZ problem. The peak magnitude and phase angle difference of voltages are the parameters to be estimated to compute the area of the ellipse. State‐of‐the‐art passive methods consider the effect of either magnitude or phase angle or frequency as an islanding detection metric. The CSoDoA metric combines the effect of both magnitude and phase angle thereby reducing the NDZ. The proposed method is validated on both synchronous and inverter‐interfaced DERs. The test systems considered are both single‐DER based MG and modified IEEE 13 bus multi‐DER MG. The CSoDoA algorithm is implemented on a Raspberry‐Pi controller and validated using HIL workbench with real‐time simulator OP‐4510. Various islanding and non‐islanding events are simulated, tested and it is evident from the results that it has a very small NDZ. Abstract : A novel CSoDoA‐based passive islanding detection for multi‐DER MG is presented in this paper. The proposed method has NDZ as low as 1% and is applicable to all types of DERs.The control algorithm of the method is implemented on a low‐cost Raspberry‐Pi controller and is validated on HIL test bench.